Mitigating adverse social and health impacts of COVID-19 with applied arts - Martina Metzger; Hans Walter Steinhauer; Jennifer Pédussel Wu (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
In this project, we analyze whether the arts can mitigate negative impacts of social distancing and isolation on mental health and wellbeing, ease the burden of closed day-care and school facilities on families, and preserve attitudes of solidarity and trust. Using the SOEP-CoV questionnaire, we examine whether experience with music enabled individuals and households to handle social isolation and distancing rules and requirements better than their peers without this artistic experience. Research has shown that persistent shocks on income have a significant impact on happiness and hence on social and health well-being, thus, we explore the importance of music in this context. Using discrete choice econometric estimation techniques, this paper finds that music does indeed mitigate the negative impact of prolonged social distancing proxied for by life satisfaction. In addition, musical practice leads to feelings of less social isolation during this period.
Keywords: Z11; I00; D1; C23; 330; Covid-19 Pandemic; Music; Happiness; Isolation Panel